Anxiety among Nurses in East Java Indonesia: A Comparative Study between Nurses Working in Primary Health Centers and Hospitals - Heni Dwi Windarwati; Tantut Susanto; Budi Anna Keliat; Hanik Endang Nihayati; Retno Lestari; Adji Achmad Rinaldo Fernandes; Niken Asih Laras Ati; Mira Wahyu Kusumawati (Nurse Media Journal of Nursing, 2026)
Background: Nurses experience considerable psychosocial demands that may contribute to anxiety symptoms. Work settings and work schedules, particularly shift work, may be important contributing factors. However, evidence comparing anxiety symptoms across healthcare settings and examining associated demographic and occupational factors among nurses in Indonesia remains limited.Purpose: This study examined anxiety symptoms among nurses working in primary health centers and hospitals in East Java, Indonesia, and identified associated demographic and occupational factors.Methods: A descriptive cross-sectional study was conducted among 315 nurses working in primary health centers and hospitals in East Java, Indonesia. Anxiety symptoms were assessed using the Generalized Anxiety Disorder-7 (GAD-7). Descriptive statistics were used to summarize participant characteristics and the prevalence of anxiety symptoms. The Mann–Whitney U test, chi-square test, and Fisher’s exact test were used to examine differences and associations between demographic and occupational characteristics and anxiety symptoms.Results: Among 315 nurses, 72.1% worked shifts. Participant characteristics differed significantly by workplace in terms of age (p = 0.002), years of experience (p = 0.001), location (p = 0.001), marital status (p = 0.003), income (p = 0.038), and work schedule (shift vs. non-shift; p = 0.001). Anxiety symptoms (GAD-7 ≥ 7) were significantly associated with age (p = 0.001), years of experience (p = 0.008), marital status (p = 0.003), income (p = 0.001), and work schedule (p = 0.006). Hospital nurses had higher odds of experiencing anxiety symptoms than nurses working in primary health centers (OR = 4.842; p = 0.010). Shift work was also associated with higher odds of anxiety symptoms (OR ≈ 6.8) compared with non-shift work.Conclusion: Hospital work and shift work were associated with anxiety symptoms among nurses, along with demographic factors such as younger age, shorter work experience, unmarried status, and lower income. These findings support targeted anxiety screening and workplace interventions, including shift management and psychosocial support, particularly for hospital nurses.